BANKING EFFICIENCY ANALYSIS OF CONVENTIONAL AND ISLAMIC BANKS IN INDONESIA USING DATA ENVELOPMENT ANALYSIS - Azhahra, Devi Rizkia; Aliludin, Arson (Journal of Business and Management, 2018)
Abstract - Banking is one of the pillars of economic growth and national stability to improve people's lives from the financial sector. If we look at the history of Indonesian banking, conventional banks were operated much earlier than Islamic bank. Islamic bank was newly established on 1992 while Conventional banks was operated longer than Islamic Bank. Until now, banking industry in Indonesia is dominated by the conventional banking market. But along with the development of the banking world and the needs of the muslim majority in Indonesia to obtain financial services that are based on the principles of Islam which is the principle of profit sharing, the government published the Act No.7 of 1992 on banking. In conducting its operational activities the bank must work efficiently in order to grow faster and survive amid market competition.Â  In such circumstances, the assessment of bank efficiency becomes important since efficiency is a performance picture of the bank.This study measure VRS efficiency and CRS efficient of two group of banks that are conventional banks and islamic banks in Indonesia for period 2012-2017. The method used is non-parametric frontierÂ  method using data envelopment analysis (DEA) with three input variables, total deposit, labor cost and fixed assets and two input variable, total loans and total income. This study used intermediation approach with output orientation. The finding of the study show that conventional banks were more efficient rather than Islamic banks.Keywords: Banking Industry, Efficiency, Data Envelopment Analysis, Output-orientation, Intermediation Approach